Lebih Lekat, Lebih Berharga: Peran Parent dan Peer Attachment terhadap Self-Esteem Remaja dengan Orang Tua Bercerai di Kabupaten Karawang - Kartika, Kiki Sri; Riza, Wina Lova; Aisha, Dinda (Universitas Muhammadiyah Metro, 2024)
The purpose of this research is to knowing an effect of parent and peer attachment of self-esteem. Participants in this research were adolescents with divorced parents aged 13 until 21 years old in Karawang Regency with total of 204 participants, 47 men and 157 women. The sampling uses convenience sampling technique. The data collected tools using the Inventory of Parent and Peer attachment (IPPA) scale and the Rosenberg Self-esteem Scale (RSES) with quantitative methods. Data analysis using multiple regression hypothesis techniques using the SPSS program version 25.0 for windows 64-bit. Data analysis shows the significance value of regression from parents and peer attachment to self-esteem is 0.000 which means there is an effect of parent and peer attachment on self-esteem of adolescents with divorced parents in Karawang Regency. The results of the coefficient of determination of parent and peer attachment to self-esteem is (R Square) 0.117 or 11,7%, where parent attachment contributes 4,2% while peer attachment 7,5%, it's mean that peer attachment has a higher effect than parent attachment on the self-esteem of adolescents with divorced parents in Karawang Regency.